Magnetic investigations of Mn-based and Mn-free potential half metals - Zhang, Rui (Trinity College Dublin. School of Physics. Discipline of Physics, 2022)
This thesis is concerned with an unusual category of magnetically ordered material, the zero moments ferrimagnetic half metal, which has potential for applications in thin film memory and logic devices. The materials are all prepared in bulk form. Due to the problem of Mn diffusion into the MgO tunnel barriers in thin film devices, it is necessary to explore compensated ferrimagnetic Mn-free half metals. Chapter 1 starts with the introduction of magnetism, including its history over the centuries and the main concepts of magnetism in solids, consisting of magnetic interactions, crystal field, critical behaviour etc. One type of magnetic material we are especially interested in is half-metal, showing 100% spin polarization. It has a band gap, behaving like an insulator, in one spin channel, while in the other one, it shows a non-zero density of states at the Fermi level. As a family of half-metals, the Heusler-type alloys with high Curie temperature are promising. The development of spintronic materials would boost non-volatile memory expansion in limited space, like magnetic random-access memory. Chapter 2 is related to experimental procedures which were used during the investigations, including arc-melting, chemical vapour transport method, annealing treatments, x-ray diffraction, SQUID magnetometry, Mössbauer spectroscopy and point contact Andreev reflection measurement (PCAR). In chapter 3, rare-earth-free ferrimagnets Mn4-xZxN (Z = Cu Ge and Ag Sn) were investigated, which exhibit a magnetic compensation at room temperature. Compensated ferrimagnets exhibiting the characteristics of antiferromagnets (zero moments) and ferromagnets (transport properties) create opportunities for applications in high-frequency spintronics and low-energy loss communications. Apart from the traditional linear antiparallel alignments of sublattices, the non-collinear frustrated 2.35 µB moments of Mn on 3c sites of the (111) Kagome planes tilt about 20° out-of-plane in Mn4N and are easily influenced by substitutions on 1a sites, leading to different efficiency of compensation in Mn4-xZxN. The manganese site moments are determined by Z, orbital hybridization, charge transfer and the tilt angle, analysed by constrained density functional theory. The Ga compound with compensation at room temperature for x ≈ 0.26 we recommend for high-frequency spintronic applications. However, the spin polarization of those ferrimagnets can never achieve the ideal value (100%) indicated by the band structures of the non-collinear Mn4N ferrimagnets calculated by Dr. Zsolt Gercsi. Fully compensated ferrimagnetic half-metals are required for low energy loss communications and high frequency spintronics. They are magnetically ordered materials that show ideal spin polarization with zero stray fields. The crystallographically inequivalent magnetic sublattices with the antiparallel alignment of their spins lead to compensated ferrimagnetism with no net magnetization. In chapter 4, Mn-based Heusler ferrimagnetic half metals are developed by two methods. One is tuning the Fermi level by doping V into Mn2FeAl to obtain the same electron states in two spin channels, leading to zero moments. The other one is combining two half metals with magnetic moments of opposite signs (one with Zt = 22, Mn2VAl; the other with Zt =25, Mn2FeAl)) to obtain a fully compensated ferrimagnetic half metal. These ideal half metals are potential candidates for spintronic devices. Up until now, we have developed three Mn-based ferrimagnets with low moments, but unfortunately, the problems of Mn diffusion into the tunnel barrier in thin film devices have been discussed recently. We then moved to explore Mn-free alloys in chapter 5. Four Mn-free binary (V3Al/Ga) and quaternary Heuslers (CrVTiAl/Ga) with 18 valence electrons and ideally ordered crystal structures, which have been theoretically predicted to be zero-moment half metals or spin gapless semiconductors, are studied experimentally. Experiments show that highly ordered quaternary structures cannot be obtained in bulk materials, consistent with the calculated Hull distance that provides an idea of the absolute phase stability. Further study on the magnetism of itinerant elements, e.g. V, Pt, provides an idea to develop new Mn-free ferrimagnets by controlling the itinerant elements bond length. Chapter 6 investigates the critical behaviour and first-order transition in the low-spin pyrite CoS2, which was recently identified as a topological ferromagnet with high spin polarization. Tricritical behaviour observed in scaling plots that indicates the appearance of ferromagnetism in CoS2 is a first-order phase transition. Critical exponents β = 0.196, γ = 0.972 and δ = 5.27 do not obey the Widom equality which suggests a first-order transition. Finally, in chapter 7, the results were summarized, and future work is described.
APPROVED
Keywords: Mn-based; Mn-free; ferrimagnet; half metal